Numerical simulation of transpiration cooling on stagnation line in thermochemical non-equilibrium - Brody, S; Lau, KS; Clarke, J; McGilvray, M; Di Mare, L (Aerospace Research Central, 2024)
Sharp leading edges offer drag and maneuverability advantages for hypersonic applications such as powered flight and some gliding trajectories. The reduction in standoff distance resulting from the adoption of sharp edges, however, results in increased surface convective heating that needs to be managed. Ablative layers are unfeasible as a cooling strategy for sharp edges because they lead to a change in surface curvature radius and render systems non-reusable. Among possible strategies, transpiration cooling has been presented as an attractive option in terms of cooling effectiveness and system complexity. In this study, a method is presented for the numerical simulation of transpiration cooling in proximity of the stagnation point of sharp leading edges or tips. The method is suited to both equilibrium and non-equilibrium flight regimes and is based on stagnation line theory presented by Cheng. Transport properties are determined through rigorous Chapman-Enskog theory. Non-equilibrium cases are handled with Park’s two temperature model. The solver explicitly represents coolant flow through a porous medium. Detailed temperature profiles and mole fractions in the shock layer and within the porous medium can be evaluated, with variations in in these profiles computed as functions of flight altitude, speed, leading edge radius, and coolant flow rate and composition. Argon, helium, and nitrogen are tested for their efficacy. The ability of different coolant mixtures to limit the transport of catalytic species to the surface is studied.